2022
DOI: 10.1111/1365-2435.14186
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical trait filtering at different spatial scales determines beetle assemblages in deadwood

Abstract: 1. Environmental filters-including those resulting from biotic interactions-play a crucial role during the assembly of ecological communities. The importance of scale has thereby been acknowledged but filters at different scales have rarely been quantified in relation to each other, although these hierarchically nested filters eventually determine which communities assemble from a regional species pool.2. Saproxylic beetles offer an ideal system to study such hierarchically nested environmental filters. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Additionally, we found that the roundness of the saproxylic beetle's body was predictive of forest naturalness. Other research has found some indication that beetle body shape responds to forest structure (Barton et al, 2011;Micó et al, 2020;Hagge et al, 2021;Neff et al, 2022;Traylor et al, 2023), and this is enough to indicate that there may be an important mechanism at work. However, which mechanisms underlie this trait in relation to forest structure remain an open question.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Additionally, we found that the roundness of the saproxylic beetle's body was predictive of forest naturalness. Other research has found some indication that beetle body shape responds to forest structure (Barton et al, 2011;Micó et al, 2020;Hagge et al, 2021;Neff et al, 2022;Traylor et al, 2023), and this is enough to indicate that there may be an important mechanism at work. However, which mechanisms underlie this trait in relation to forest structure remain an open question.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings also indicate that species with reduced dispersal ability are sensitive to intensive forest management. Research has also found that traits related to dispersal ability, including wing length, decreased with the proportion of broadleaf trees (Neff et al, 2022). Neff et al (2022) suggest that the mechanism behind this result is that conifers have been relatively recently introduced into Central Europe for forestry purposes, and conifer specialists with low dispersal abilities have not been able to establish themselves yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to mechanisms acting at the deadwood‐log scale, community assembly of saproxylic communities is affected by spatial processes and environmental conditions (Neff et al, 2022). The composition of saproxylic communities varies spatially with beta‐diversity increasing with increasing spatial distance between deadwood logs both within (Bae et al, 2020; Müller et al, 2020) and among regions (Bae et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to mechanisms acting at the deadwood-log scale, community assembly of saproxylic communities is affected by spatial processes and environmental conditions (Neff et al, 2022).…”
Section: Introductionmentioning
confidence: 99%